Edukasi herbal dan pengolahan minuman herbal sebagai peningkat sistem imun untuk mencegah infeksi COVID-19 - Indah Solihah; Rennie Puspa Novita; Riana Sari Puspita Rasyid (INDRA: Jurnal Pengabdian kepada Masyarakat, 2022)
The COVID-19 situation at the global and national levels is still at very high risk. A good immune system is needed to protect us from COVID-19. Eating healthy meals and increasing antioxidant consumption can help us to boost the body's immune system. Some herbs in Indonesia that are useful in boosting the immune system based on the Traditional Medicine Formulary are included red ginger, lime, cinnamon, and garlic. The Red ginger rhizome contains gingerol and shogaol, cinnamon bark contains cinnamaldehyde, lime has a high vitamin C content, and garlic bulbs contain ajoene. All of these compounds can synergistically improve the immune system. These ingredients are widely available and are processed into antioxidant herbal drinks that increase the immune system. The activity was carried out using the lecture method, discussion, and pretest-posttest to measure the level of participant knowledge. After the implementation of the activity, public knowledge increased regarding herbal ingredients, their processing, and preparation. As many as 100 percent of respondents were recognized the types of immune system enhancing herbs, 72 percent were understood how to process herbs, and 92 percent were understood how to prepare these herbs.